OPTIMIZATION OF LEARNING AT SMP LABUHANHAJI RAYA IN SOUTH ACEH THROUGH MERDEKA MENGAJAR AND LEARNING MEDIA - Anhar, Anhar; Rahmatullah, Rahmatullah; Sariakin, Sariakin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to investigate the influence of using the Merdeka Mengajar Platform (PMM) and utilizing instructional media on the quality of education at SMP Labuhanhaji Raya, South Aceh. The research employs a quantitative approach with a correlational design. Teachers constitute the population of this study, totaling 200 individuals, from which a proportional random sample of 133 teachers was selected. Data were collected using a questionnaire. The results indicate that PMM and the use of instructional media simultaneously affect the quality of education at SMP Labuhan Haji Raya, South Aceh, with a significance value of 0.000 < 0.05. Students who use PMM and instructional media tend to have better conceptual understanding and higher engagement levels in the learning process. Furthermore, teachers who utilize instructional media in delivering content demonstrate better skills in capturing students' attention and explaining material more effectively. This research provides important insights for educational practitioners and policymakers regarding the significance of integrating technology and instructional media to enhance the quality of education in schools. Practical implications of this study include recommendations for enhancing teacher training in utilizing instructional media and developing teaching strategies that integrate PMM with existing instructional methods.